Culture and History in the Pacific - Siikala, Jukka (Helsinki University Press, 2021)
Culture and History in the Pacific is a collection of essays originally published in 1990. The texts explore from different perspectives the question of culture as a repository of historical information. They also address broader questions of anthropological writing at the time, such as the relationship between anthropologists' representations and local conceptions. This republication aims to make the book accessible to a wider audience, and in the region it discusses, Oceania. A new introductory essay has been included to contextualize the volume in relation to its historical setting, the end of the Cold War era, and to the present study of the Pacific and indigenous scholarship. The authors of Culture and History in the Pacific include prominent anthropologists of the Pacific, some of whom - Roger Keesing and Marilyn Strathern, to name but two - have also been influential in the anthropology of the late 20th and early 21st century in general.